Gravitational waves and magnetic monopoles during inflation with Weitzenböck torsion - Romero, Jesús Martín (2016)
We study the variational principle on a Hilbert-Einstein action in an extended geometry with torsion taking into account non-trivial boundary conditions. We obtain an effective energy-momentum tensor that has its source in the torsion, which represents the matter geometrically induced. We explore about the existence of magnetic monopoles and gravitational waves in this torsional geometry. We conclude that the boundary terms can be identified as possible sources for the cosmological constant and torsion as the source of magnetic monopoles. We examine an example in which gravitational waves are produced during a de Sitter inflationary expansion of the universe.